Abra State Institute of Sciences and Technology Cottage Rental Billing and Collection System (ASIST-CREBACS - Trinidad Jr., Joventino T. (JPAIR Institutional Research, 2015)
In most organizations, Business Information Systems (BIS) make extensive use of information technology, such as personal computers. The study identified the ASIST cottage rental policies and procedures done in billing and collection of rental fees as a basis in developing the ASIST-CREBACS and evaluated the usability of the developed system in terms of usefulness, ease of use, ease of learning, and satisfaction. The study used the descriptive-applied type of research applying the Extreme Programming (XP) model. The researcher used Visual Basic 2008 which supports the Microsoft with NET framework as the programming language and My Standard Query Language (MySQL) as the relational database. Total enumeration of eight staff in the Cashiering and Accounting Offices including the cashier, the accountant, three collecting officers, and three billing clerks evaluated the usability of the developed system. The study used documentary analysis, interview, and the Usefulness, Satisfaction and Ease of Use (USE) questionnaire as data gathering instruments. The cottage rental policies are based on ASIST Implementing Order No. 023, Series of 2009 and the procedures done in billing and collection of rental fees are done semi- manually. Â As a result, the ASIST-CREBACS was conceived and developed. The ASIST-CREBACS was designed to fit the cottage rental policies and procedures done in billing and collection of rental fees because it was found to be usable.
Keywords: Cottage Rental; Billing; Collection; Extreme Programming (XP); Usefulness Satisfaction and Ease of Use (USE); descriptive-applied design; Philippines; Asia